Facilely prepared carbon dots and rare earth ion doped hybrid composites for ratio-metric pH sensing and white-light emission. Issue 66 (28th June 2016) - Zhang, Tianxiang; Zhai, Yue; Wang, He; Zhu, Jinyang; Xu, Lin; Dong, Biao; Song, Hongwei
Abstract : A facile method was developed to synthesize fluorescent carbon-dot–Eu 3+ hybrid composites (CD–Eu–HCs) by one-pot hydrothermal methods. Abstract : A facile method was developed to synthesize fluorescent carbon-dot–Eu 3+ hybrid composites (CD–Eu–HCs) by one-pot hydrothermal methods. The prepared composites demonstrate unique dual fluorescence which originates from the blue emission of the CDs and intrinsic photoluminescence of the Eu 3+ ions, respectively. Moreover, such dual fluorescent characteristics show quite different responses for different pH value environments and have been developed in a ratiometric pH sensor. Lastly, they can realize white light emission by co-doping of Tb 3+ and the color temperature becomes tunable by adjusting the relative proportion of Eu 3+ .